PELATIHAN PEMBUATAN PRODUK DIGITAL DAN TEKNIK PEMASARANNYA BAGI GURU SD ISLAM MAHAD DARUSSALAM - Hera Febria Mavilinda; Yulia Hamdaini Putri; Yusuf Radityawan Idrad; Tika Rahma Yani Siregar; Alditya Aris Rinandy (Universitas Mataram, 2026)
The advancement of digThe advancement of digital technology has significantly transformed the realm of education, especially in the creation and distribution of instructional materials. Elementary school educators must exhibit greater creativity and adaptability in developing engaging, interactive learning materials that align with the features and requirements of contemporary pupils. Nevertheless, numerous elementary school educators in the domain remain deficient in the competencies required to develop high-quality digital educational materials, such as e-books and worksheets, and lack comprehension of digital marketing strategies to enhance the visibility of their goods. This service program provides training for the development of two categories of digital products: worksheets derived from primary school curricula and fundamental digital marketing strategies. The techniques for implementing the activities encompass socializing, training, and mentorship. The activity's results indicate that the teachers successfully developed e-books and worksheets and effectively promoted the products via their social media platforms. ital technology has significantly transformed the realm of education, especially in the creation and distribution of instructional materials. Elementary school educators must exhibit greater creativity and adaptability in developing engaging, interactive learning materials that align with the features and requirements of contemporary pupils. Nevertheless, numerous elementary school educators in the domain remain deficient in the competencies required to develop high-quality digital educational materials, such as e-books and worksheets, and lack comprehension of digital marketing strategies to enhance the visibility of their goods. This service program provides training for the development of two categories of digital products: worksheets derived from primary school curricula and fundamental digital marketing strategies. The techniques for implementing the activities encompass socializing, training, and mentorship. The activity's results indicate that the teachers successfully developed e-books and worksheets and effectively promoted the products via their social media platforms.